The impact of social media usage towards hotels’ performance / Valeria Jainol and Christie Umang Sakai Pengiran - Jainol, Valeria; Pengiran, Christie Umang Sakai (2019)
The purpose of this study was to determine the impacts of social media towards the hotel and also to identify the most prominent social media impact that hotel always earned. The research design for this study was an argumentative study. The approach that was used to collect accurate data was by using a theoretical framework. Besides that, this study also employed the secondary data to make a review from the past researchers' journal article, study and other sources. The type of secondary data that was used for this study was journaling article. The most prominent secondary data researchers used in this study as the primary references were the journal articles. The examples of journal article used were mostly from International Journal of Contemporary Hospitality Management, Journal of Hospitality and Tourism Technology and Global Journal of Human-Social Science: Economic, International Journal of Business and Management Invention and others. At the end of this study, we concluded that effective communication and informative were the prominent social media impact that hotel always earned. Besides, other social media impacts were also still important to hotel organization and had their way to give positive impact to hotel. Adding to that, the source of data use for literature review was from a wide range of geographic. It did not focus on a specific location. This is because, there might be a difference in variable (social media impact) in a specific region. The findings of this study enabled hoteliers to understand the implementation of social media could affect the hotel, strategize hotel management using social media and also as a benchmark (industry perspective).